Fatal outcome related to drug reaction with eosinophilia and systemic symptoms: a disproportionality analysis of FAERS database and a systematic review of cases - Liang, Chunsu; An, Pengjiao; Zhang, Yizhou; Liu, Xin; Zhang, Bo (Frontiers in Immunology, 2024)
BackgroundDrug rash with eosinophilia and systemic symptoms (DRESS) is a life-threatening severe cutaneous adverse reaction.ObjectiveThis study aims to study fatal DRESS cases using FAERS database and systematic review.MethodsData of the FDA Adverse Event Reporting System (FAERS) database were extracted and manipulated. Articles from Pubmed, Embase and CINAHL databases were screened.Results0.13% of the adverse events submitted to FAERS was identified as DRESS and the percentage of fatal cases was up to 6.62%. The top five drugs calculated to induce DRESS with the highest number of reported cases were allopurinol, lamotrigine, vancomycin, amoxicillin and carbamazepine. The top five drugs statistically related to fatal outcome with the highest number of reported cases were allopurinol, vancomycin, trimethoprim, sulfamethoxazole and lamotrigine. Skin manifestations remained the main reason for admission and the average time from dose to rash onset was 27.19 days. The most commonly cited culprit medication type were antibiotics (50.00%), anti-gout agents (15.38%) and anti-epileptic drug (11.54%).ConclusionsWe discussed fatal cases of DRESS through FAERS system and case reports, hoping to raise awareness when using relevant drugs.